The Effect of Alkali Activator Ratio on Mechanical Properties Geopolymer Concrete Based on Ground Granulated Blast Furnace Slag - Lianasari, Angelina Eva; Naufal Muhammad Syafig, (International Journal of Sustainable Construction Engineering and Technology, 2023)
Cement is the primary material of concrete. In the calcination process during cement manufacturing, 0.869 tons of CO2 gas are produced for every 1 ton of clinker. That process affects global climate change. This condition causes a new technology called geopolymer concrete. Geopolymer concrete substitutes cement with material that reacts in an alkali activator. PT Krakatau Steel in West Java, manufacturing iron steel with a blast furnace, produces large quantities of waste (slag) of 80 tons/hour. The blast furnace slag contains SiO2 and Al2O3 is called GGBFS (Ground Granulated Blast Furnace Slag). GGBFS can react with an alkali activator, which can be a substitute cement. This research was carried out using GGBFS as a base for geopolymer concrete. This research wants to know the effect of the alkali activator ratio on the mechanical properties of geopolymer concrete based on GGBFS. The concrete specimen was made with ratios alkali activator of 5:2, 4:2, and 3:2. The alkaline liquids used in this research are sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) with a concentration of 8M. The curing process in this experiment is about 24-hour dry curing at a temperature of 60oC. The mechanical properties of concrete showed that 5:2 obtained the highest compressive strength, 57.65 MPa (at 7 days) and 58.48 MPa (at 28 days), and modulus elasticity was 31815.92 MPa, split tensile strength was 2.74 MPa, and modulus of rupture was 3.87 MPa